Conservation of spider diversity within an agricultural mosaic : insights from the Greater Cape Floristic Region, biodiversity hotspot. - Theron, Kasselman Jurie (Stellenbosch : Stellenbosch University, 2017)
Thesis (MScConsEcol)--Stellenbosch University, 2017.